Shot peening in a novel centrifugal air blast reactor. (2nd September 2017) - Ranaware, P. G.; Rathod, M. J.
ABSTRACT: A novel reactor to synthesise a thick nanocrystalline (NC) layer on metallic surface by shot peening is presented. In this cylindrical reactor, air enters inside the reactor tangentially and propels shots on specimen surface for peening. The air then leaves the reactor after multiple rotations. Air vortex and very high turbulence inside the reactor dissipate the heat generated during shot peening and thus avoids dynamic recovery. Experiments were conducted on samples of austenitic stainless steel with different shot velocities. Characterisation of shot peened surfaces showed that thick layers with NC/nano-twinned structure were developed under all peening conditions used in the experiments. Microstrain in the lattice, dislocation density and volume fraction of strain-induced martensite observed to increase with rise in shot velocity. Consistent reduction in grain size and enhancement in dislocation density with increase in strain, indicate that no dynamic recovery occurred during the shot peening process in the reactor.